(untitled) (Research, Society and Development, 2022)
Objective: To measure the level of knowledge of women who live in Curitiba and who have already gone through the gestational period about the OV committed by health professionals such as doctors, nurses, nursing technicians and others. Methodology: This is a prospective field research using a quantitative method, carried out via a WhatsApp link. For data collection, a questionnaire with twenty objective, non-invasive, simple questions was applied from August to September 2022. Results: It was observed that the interviewees had a good level of knowledge of the VO indicators. Finally, there was a high, and worrying, set of reports that point to a high frequency of perceptions that indicate different types of VO in pregnant women during labor. Conclusion: It was possible to conclude that women know the term obstetric violence, however, they partially know the forms of violence. It was also possible to identify that women know most of their rights during the pregnancy-puerperal cycle, which is a positive point, since most of the women interviewed were not adequately oriented during prenatal care on these topics.